A comprehensive proteome map of glandular trichomes of hop (Humulus lupulus L.) female cones: Identification of biosynthetic pathways of the major terpenoid‐related compounds and possible transport proteins. Issue 8 (April 2017) - Champagne, Antoine; Boutry, Marc
Abstract : Female flowers of hop ( Humulus lupulus ) are an essential source of terpenoid‐related compounds, which are mainly used as flavoring in the beer brewing process. The compounds involved are bitter acids, terpenophenolics, as well as mono‐ and sesquiterpenoids. In this work, we analyzed the proteome of purified glandular trichomes (lupulin glands) from female flowers, which produce and accumulate these compounds. An extensive 2D‐LC‐MS/MS analysis identified 1015 proteins. Of these, most correspond to housekeeping and primary metabolism‐related proteins, albeit predominantly including amino acid and lipid metabolism, which feeds the specialized (secondary) metabolism. Indeed, 75 proteins belong to the specialized metabolism. No less than 40 enzymes are involved in the synthesis of terpenoid‐derived compounds and 21 are predicted transporters, some of which might be involved in the transport of specialized metabolites. We discuss the possible routes involved in the intra‐ and intercellular translocation of terpenoids and their precursors. This comprehensive proteomic map of the glandular trichomes of hop female flowers represents a valuable resource to improve our knowledge on the function of glandular trichomes.